Crystal Structure and Spectroscopic Characterisation of (E)-N′-(2,4-dimethoxybenzylidene)-4-nitrobenzohydrazide (DMNBH): A Combined Experimental and DFT Investigation of its Electronic and NLO Properties - Sumathi, B.; Vijayalakshmi, V.; Sabari, V.; Sankar, S.; Kanagathara, N. (Asian Journal of Chemistry, 2026)
The hydrazone derivative of (E)-N'-(2,4-dimethoxybenzylidene)-4-nitrobenzohydrazide (DMNBH) was synthesised and characterised experimentally by using single-crystal X-ray diffraction, FT-IR and UV-Vis spectroscopy. XRD established the molecular configuration and crystal packing, supported by intermolecular interactions. FT-IR analysis confirmed the formation of the azomethine (C=N) group along with methoxy and nitro functional groups. UV-Vis spectroscopy showed characteristic π→π* and n→π* transitions attributed to the donor–acceptor framework of the molecule. Density functional theory (DFT) calculations at the B3LYP/6-311++G (d,p) level optimised the molecular geometry and simulate vibrational frequencies, showing good agreement with experimental FT-IR results. Hirshfeld surface analysis and energy framework calculations quantified intermolecular interactions within the crystal lattice. Frontier molecular orbital (HOMO–LUMO) and MEP, indicating intramolecular charge transfer between the donor and acceptor unit. Natural bond orbital (NBO) analysis confirmed effective charge delocalisation and the calculated first-order hyperpolarizability demonstrated the molecule’s nonlinear optical (NLO) response. In addition, molecular docking studies were performed to evaluate the biological affinity of DMNBH, revealing favourable binding interactions with the target protein.